Possibilities of conceptualization and operacioanlizaton of the safety culture and safety climate in the international safety management researches - Terjék, László (Acta Agraria Debreceniensis, 2009)
In this paper the author summarized the definitions and operationalisations of the safety culture and safety climate concepts. He analyzed the Hungarian and international safetymanagement scientific literatures. He also analyzed the scientific definitions and summarised the common and different elements. The author emphasizes that the many different scientific safety culture researches had been created good possibilities to find the common surfaces. Based on the international safety culture operationalisation practices the author identified a composition of safety culture dimensions which could be a possible basis for the Hungarian safety culture researches. These dimensions are:???? values (individual and organizational) from this result scale of values,???? attitudes (individual and organizational),???? motivations,???? perceptions,???? social status and estimation of the occupational safety and health,???? position and estimation of the occupational safety and health communication,???? position and estimation of the occupational safety and health tranings,???? measuring of confidence, optimism, fatalism and anomic characteristics,???? good practices and behavior,???? influence and estimation of the work,???? risk perception and safety level perception,???? contentment.with occupational safety and health.